Studi Multisitus Tantangan Guru PAI dalam Mengajarkan Akhlak di Era Modernisasi di Kecamatan Bangunrejo - Ulin Nuha (Departement of Mathematics Education, 2024)
This study aims to identify the challenges faced by Islamic Religious Education (PAI) teachers in teaching ethics in the era of modernization, as well as to explore the strategies they use to overcome these challenges. This research employs a qualitative approach with a case study method, involving 8 PAI teachers from 4 different secondary schools in Bangun Rejo District. Data was collected through in-depth interviews, participatory observation, and documentation. The results show that the main challenges faced by PAI teachers include internal factors such as motivation and limited knowledge about Islamic ethics, and external challenges such as the influence of global culture, parental involvement, and school support. To overcome these challenges, teachers apply various strategies, including improving professionalism through training, utilizing technology in teaching, and collaborating with the school, parents, and the community. The study concludes that a combination of enhancing teachers' skills and environmental support is crucial to ensuring the success of teaching Islamic ethics in the modern era.